2022
DOI: 10.1002/eqe.3697
|View full text |Cite
|
Sign up to set email alerts
|

Lid induced sloshing suppression and evaluation of wall stresses in a liquid storage tank including seismic soil‐structure interaction

Abstract: Aboveground liquid storage tanks are often found on weak compressive soil due to their proximity to harbours and rivers. These soil conditions lead to a high probability of significant soil‐structure interaction (SSI) under earthquake loading. In strong earthquakes, the transient partial separation of the tank base from the supporting medium (uplift) and chaotic liquid sloshing often cause damage to the tank wall. This experimental research determines the simultaneous effects of SSI and the restriction of slos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Experimental studies have also been performed to reveal the influence of the rocking footing. Research by Hernandez-Hernandez et al, 21,22 for example, investigated the influence of rocking on the seismic behaviour of water tanks. Their result showed that the flexibility of the support has different influences on the top displacements and accelerations of tanks depending on the slenderness.…”
Section: Noveltymentioning
confidence: 99%
“…Experimental studies have also been performed to reveal the influence of the rocking footing. Research by Hernandez-Hernandez et al, 21,22 for example, investigated the influence of rocking on the seismic behaviour of water tanks. Their result showed that the flexibility of the support has different influences on the top displacements and accelerations of tanks depending on the slenderness.…”
Section: Noveltymentioning
confidence: 99%
“…19,21 The seismic performance of structures depends on the ground motion intensity, as was also observed for storage tanks. 7,12,16,20 It is known that ground motion intensity at the site is, to some extent, affected by the site properties 23 Passeri et al 24 reported that the soil deposit properties affect the site response and the seismic action at the ground surface and thus, for example, at the structure foundation elevation. However, the authors used different ground motion intensity measures (IMs) for seismic hazard study.…”
Section: Introductionmentioning
confidence: 99%
“…In severe destructive earthquake disasters, liquid storage tanks will not only cause severe direct damage, but also will be highly likely to induce more serious secondary disasters. For example, a large number of oil storage tanks were damaged and caused explosions and fires in the 1994 Niigata earthquake in Japan, a large number of water storage tanks were damaged in the 1976 Tangshan earthquake in China, causing drinking difficulties for residents, and the leakage of nuclear material storage tanks at the Fukushima nuclear power plant in the 2011 earthquake in Japan has now threatened the global ecological environment, etc [2][3][4]. The liquid medium in the storage tank will generate hydrodynamic pressure under the action of seismic force, compared with other solid structures, the damage mechanism of liquid storage tank under seismic force is relatively more complex.…”
Section: Introductionmentioning
confidence: 99%